Condylomata Acuminata (Anogenital Warts) Contain Accumulations of HIV-1 Target Cells That May Provide Portals for HIV Transmission. (20th August 2018) - Pudney, Jeffrey; Wangu, Zoon; Panther, Lori; Fugelso, Dana; Marathe, Jai G; Sagar, Manish; Politch, Joseph A; Anderson, Deborah J
Abstract : Anogenital warts contain significantly higher concentrations of human immunodeficiency virus (HIV)–target cells than site-matched normal skin. These findings provide biologic evidence that anogenital warts may promote HIV sexual transmission and suggest that prevention or treatment of anogenital warts could decrease HIV transmission. Abstract: Background: Condylomata acuminata (anogenital warts [AGWs]) are prevalent in human immunodeficiency virus (HIV)–infected individuals and sexually active populations at risk for HIV acquisition and have been associated with HIV transmission. We compared AGW specimens to control tissue specimens for abundance, types, and location of HIV target cells and for susceptibility to HIV infection in vitro, to provide biologic evidence that AGWs facilitate HIV transmission. Methods: We used immunohistologic staining to identify HIV target cells in AGW and control specimens. We also inoculated HIV in vitro into AGW and control specimens from HIV-negative men and assessed infection by means of TZM-bl and p24 assays. Results: CD1a + dendritic cells, CD4 + T cells, and macrophages were significantly more abundant in the epidermis of AGW specimens than control specimens. These HIV target cells also often appeared in large focal accumulations in the dermis of AGW specimens. Two of 8 AGW specimens versus 0 of 8 control specimens showed robust infection with HIV in vitro. Conclusions: Compared with normal skin, AGWs contain significantly higher concentrations of HIV target cells that may be susceptible to HIV infection. Condylomata may thus promote HIV transmission, especially in the setting of typical lesion vascularity and friability. Prevention or treatment of AGWs may decrease the sexual transmission of HIV.